Seroprevalence of coxiellosis in cattle, sheep and people in the east of Turkey - Çetinkaya, B; Kalender, H; Ertas, HB; Muz, A; Arslan, N; Ongor, H; Gurçay, M (British Veterinary Assoc, 2000)
Serum samples collected randomly from 416 cattle in 48 herds, and 411 sheep in 47 flocks, in eight different locations in the east of Turkey between lune and December 1998, were examined by indirect fluorescent antibody test (IFAT) to determine the prevalence of Q fever. The age, sex, breed, tick control and abortion history of the animals were also recorded. In addition, 102 serum samples were collected from apparently healthy people who were at risk of contracting the disease, such as farmers, veterinarians, abattoir and laboratory workers, and veterinary students. Seropositivity was observed in 5.8 per cent (24/416) of the cattle in 17 (35.4 per cent) of the herds and in 10.5 per cent (43/411) of the sheep in 21 (44.7 per cent) of the flocks. Eight of the 102 people were seropositive, with the highest prevalence (12.0 per cent) in farmers and abattoir workers. All the seropositive farmers had seropositive animals. None of the laboratory workers or veterinary students was seropositive.
Keywords: Linked Immunosorbent-Assay; Q-Fever; Complement-Fixation; Antibody-Response; Burnetii; Infection; Animals; Serosurvey; Abortion; Ontario